Mercury, lead, arsenic, and cadmium in Norwegian seafood products and consumer exposure. Issue 2 (2nd April 2020) - Næss, Synnøve; Aakre, Inger; Lundebye, Anne-Katrine; Ørnsrud, Robin; Kjellevold, Marian; Markhus, Maria Wik; Dahl, Lisbeth
ABSTRACT: Seafood can be a source of contaminants, which may raise health concerns. The aim of this study was to analyse the levels of inorganic contaminants in commercially available seafood products and assess consumer exposure. Commercially available samples were collected from 2015–2018 and analysed as composite samples for mercury, lead, arsenic, and cadmium, using accredited methods. Levels of cadmium, lead, and arsenic were low and human exposure of these metals would be minimal from consumption of the analysed seafood products. Mercury levels were well below the EU maximum limit for mercury in fish. However, children, who are high consumers, might be at risk of exceeding the tolerable weekly intake for methyl mercury, when eating products with the highest mercury levels. The collected data can be used for future risk-benefit assessments as intake of processed seafood products represent a large proportion of the populations' seafood intake in Europe.